Research methods in language policy and planning a practical guide - Hult, Francis M.; Johnson, David Cassels 1974- (Chichester, West Sussex [England] Wiley-Blackwell, 2015)
"This book is the first volume that is exclusively devoted to research methods in language policy and planning"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Language policy -- Research -- Methodology; Language planning -- Research -- Methodology; Language and languages -- Research -- Methodology